The rigid isomeric 5-(x-pyridyl)-1H-tetrazole ligands-directed various isopolymolybdate-based compounds: assembly, structures, and properties. Issue 1 (2nd January 2016) - Wang, Xiuli; Li, Tianjiao; Tian, Aixiang; Xu, Na; Zhang, Rui
Abstract: Two new isopolymolybdate-based metal–organic complexes, [Cu2 (2-ptz)2 (Mo4 O14 )0.5 ] (1 ) and [Cu3 (OH)2 (3-ptz)4 ( γ -H4 Mo8 O26 )(H2 O)4 ]·10H2 O (2 ) (2-ptzH = 5-(2-pyridyl)-1H-tetrazole, 3-ptzH = 5-(3-pyridyl)-1H-tetrazole), constructed from isomeric ligands with different N-donor sites were synthesized under hydrothermal conditions. In1, each [Mo4 O14 ] 4− cluster connected with six neighboring [Mo4 O14 ] 4− clusters through six binuclear [Cu2 (2-ptz)2 ] 2+ subunits to yield a 2-D layer. In2, bidentate inorganic [Mo8 O26 ] 4− anions link the trinuclear [Cu3 (OH)2 (3-ptz)4 ] clusters to construct a 1-D chain. Adjacent chains connect through Mo–N bonds between the [Mo8 O26 ] 4− anions and pyridyl groups from the trinuclear clusters to form a 2-D layer. The effect of the N-donor sites of the rigid isomeric ligands on the structures of1 and2 was discussed. The electrochemical properties and photocatalytic activities of1 and2 have also been studied. Abstract :